Validity of E-Module on Cell Material For Class XI IPA SMA / MA - Zulkhairunnas; Widiana, Rina; Yulia Sari, Liza (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
This study aims to produce a valid and practical e-module for cell material in class XI IPA SMAN 1 Pasaman. This research is development research that uses a 4D development model consisting of a definition stage, a design stage, a development stage, and a dissemination stage. This stage is limited to the development stage because it is determined by time and cost. The e-module validity test on cell material for class XI IPA SMA/MA was carried out by 3 validators, namely 2 lecturers at the PGRI University of West Sumatra and 1 biology teacher at SMA Negeri 1 Pasaman using a validity questionnaire. The results of the e-module validity test questionnaire analysis on cell material for class XI IPA SMA / MA obtained a value of 93.1% with very valid criteria. The conclusion from the research of e-module on cell material for class XI IPA SMA/MA obtained very valid results.